2015
DOI: 10.1186/s12951-015-0087-3
|View full text |Cite
|
Sign up to set email alerts
|

Effect of carbon black nanomaterial on biological membranes revealed by shape of human erythrocytes, platelets and phospholipid vesicles

Abstract: BackgroundWe studied the effect of carbon black (CB) agglomerated nanomaterial on biological membranes as revealed by shapes of human erythrocytes, platelets and giant phospholipid vesicles. Diluted human blood was incubated with CB nanomaterial and observed by different microscopic techniques. Giant unilamellar phospholipid vesicles (GUVs) created by electroformation were incubated with CB nanomaterial and observed by optical microscopy. Populations of erythrocytes and GUVs were analyzed: the effect of CB nan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 54 publications
3
8
0
Order By: Relevance
“…The unmodified carbon black showed hemolysis of 3% and the same material modified with citric acid showed a percentage of hemolysis of 1.6%. These results indicate that CB and their derivatives have no hemolytic potential and coincide with those reported by others [ 56 , 57 ]. The NY6/MCB60-1.0 and NY6/MCB60-2.0 nanocomposites (with 1 and 2 wt % of MCB, respectively) showed low percentages of hemolysis (1.8% and 2.4%).…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…The unmodified carbon black showed hemolysis of 3% and the same material modified with citric acid showed a percentage of hemolysis of 1.6%. These results indicate that CB and their derivatives have no hemolytic potential and coincide with those reported by others [ 56 , 57 ]. The NY6/MCB60-1.0 and NY6/MCB60-2.0 nanocomposites (with 1 and 2 wt % of MCB, respectively) showed low percentages of hemolysis (1.8% and 2.4%).…”
Section: Resultssupporting
confidence: 93%
“…This study suggests that the combination of the polar polymer as Nylon 6 with MCB leads to materials with low hemolytic potential, meaning that they have excellent blood compatibility. Similar conclusions were reported by Pajnic et al when studying the effect of carbon black in biological membranes such as erythrocytes, who concluded that there is no damage by the presence of agglomerates of carbon black [ 57 ].…”
Section: Resultssupporting
confidence: 85%
“…Moreover, the work of Amornwachirabodee et al 22 on the penetration of oxidized carbon black (OCBs) (prepared from commercially available CB) into cell‐sized liposomes also reported the adsorption of phospholipids on OCBs. Additionally, a study on the effect of CB incubated with giant unilamellar phospholipid vesicles (GUV) reported a decreasing number of GUV over time, 23 thus supporting our hypothesis.…”
Section: Resultssupporting
confidence: 81%
“…The exact mechanisms by which short-term exposure to high levels of PM could elevate the risk of MI remains uncertain. However, several possible mechanisms for the associations have been discussed [24,44,45], including an elevated risk of inflammation [43], increased heart rate and reduced heart rate variability [46][47][48], increased blood viscosity [49,50], hypercoagulability [51], and vasoconstriction [52].…”
Section: Discussionmentioning
confidence: 99%